Propuesta Metodológica del Entrenamiento de la Resistencia en Baloncesto mediante la Modificación de Factores Formales y Estructurales del Juego. - Sacot, A.; Escosa, J.; Latinjak, A. T. (Revista Internacional de Ciencias del Deporte, 2017)
The aim of the present study was to create a methodological proposal for coaching staff, which consist in using the game parameters during small sided games in order to integrate endurance training with technical and tactical drills in basketball. For this reason, a systematic review was carried out so as to study the changes in heart rate and game intensity depending on the game parameters used during the game situation. Different key words such as conditioning and basketball in different data bases such as Pub Med or ISI web of knowledge were checked throughout the selection process. Finally, 12 articles were included in the review showing that the modification of some game parameters such as number of players, space conditions, time aspects and game rules, can influence the orientation of the endurance training in basketball. Thereby, a methodological proposal was created to illustrate the usefulness of the different game parameters in order to control and plan the endurance training integrated with technical and tactical drills in basketball. However, the background studies of the methodological proposal should be considered since these studies only have analyzed the simple effects of the different parameters and due to the fact, future studies should study the interaction of the different parameters in order to validate the proposal. Nevertheless, it is believed that this methodological proposal can be helpful so as to integrate endurance training with technical and tactical drills.